Investigating The Nonlinear Relationship Between Cash Conversion Cycle and Profitability: Evidence From Indonesian Property and Real Estate Companies - Difa Putra Kusuma; Wisnu Mawardi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: This study investigates the nonlinear impact of the Cash Conversion Cycle (CCC) on profitability, as measured by Return on Assets (ROA), in the property and real estate sector in Indonesia.Purpose: The research aims to provide insights into financial management development, inform decision-making regarding working capital policies, and serve as a reference for further studies.Design/Methodology/Approach: The study employs dynamic panel data analysis using the Generalized Method of Moments (GMM) in EViews12. The sample includes 43 property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period, selected through purposive sampling. Data were sourced from Bloomberg, and analysis involved GMM specification tests (Arellano-Bond and Sargan Test), Wald tests, and t-statistical tests.Findings/Results: The Wald test results indicate that CCC, CCC², company size (SIZE), sales growth (GROWTH), company age (AGE), leverage (LEV), and liquidity (CR) significantly affect ROA. Additionally, the t-statistical test reveals that CCC has a significant negative effect on ROA, while CCC² has a significant positive effect on ROA, suggesting a U-shaped nonlinear relationship between CCC and profitability.Conclusion: This study confirms a U-shaped nonlinear relationship between the Cash Conversion Cycle (CCC) and profitability (ROA) in Indonesia's property and real estate sector. Balancing CCC is essential, as both excessively short and long cycles affect profitability differently. Additionally, company size, sales growth, age, leverage, and liquidity significantly influence ROA. These findings emphasize the importance of strategic working capital management to optimize financial performance.Originality: This research contributes to the literature on working capital management by identifying a U-shaped nonlinear relationship between CCC and profitability, emphasizing its practical implications for financial decision-making in emerging markets. Keywords: facultative administration, FMEA, operational risk, Pareto diagram, risk priority